VOIDANCE DENGAN PROFITABILITAS, SIZE DAN LEVERAGE SEBAGAI VARIABEL KONTROL: Studi Kasus pada Perusahaan Manufaktur Sub Sektor Otomotif yang terdaftar di BEI Periode 2008-2017 - Pangestu, Sri Hardiyati; Pratomo, Dudi (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2020)
Tax avoidance (tax avoidance) is a process that controls an action to avoid unwanted taxation. This tax avoidance is a legal action, so that no one will break the law and will save on tax costs. The practice of tax avoidance has a negative impact on government, because tax collection on it is not optimal. This study aims to analyze Accounting Accounting and Capital Intensity towards tax avoidance with the control variables Profitability, Size, and Leverage. The population of this research is the automotive sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2008-2017. This study uses purposive sampling and obtained 4 (four) companies in automotive companies with a collection period of 10 (ten) years so that in this study obtained 40 sample units. This research uses panel data regression analysis method. The results showed that accounting conservatism, capital intensity, profitability, size, and leverage simultaneously affect tax avoidance. Partially capital intensity negatively influences tax avoidance, while accounting conservatism, profitability, size, and leverage do not affect tax avoidance. Keywords: Tax Avoidance, Accounting Conservatism, Capital Intensity. Profitability, Size, Leverage